Relationship of NLR and PLR with fracture severity in patients with proximal femur fractures (Annals of Medical Research, 2022)
Aim: The aim of this study is to investigate the role of hematological markers in predicting the severity of proximal femur fractures, which is an important mortality and morbidity problem.Materials and Methods: Patients who applied to our clinic for proximal femur fracture for 2 years between 2017 and 2019 were included in this study. Demographic information, fracture severity, fracture classification and blood values of the patients were recorded. Patients with proximal femoral fractures who were registered in the hospital information operating system and accepted to participate in this study were included in the study, while patients with a concomitant fracture, a history of malignancy, and those who applied for revision surgery were excluded from the study.Results: A total of 89 patients with proximal femoral fractures, 51 of whom were women (57.3%), with a mean age of 79.2±10.9 (range, 25 to 98) years were included in this study. The patients were divided into two groups as stable and unstable according to the severity of the fracture. When the preoperative hemogram parameters of the patients were examined, it was noted that the neutrophil (p=0.013), lymphocyte (p=0.012), Neutrophil/Lymphocyte ratio (NLR) (p=0.001) and Platelet/Lymphocyte ratio (PLR) (p=0.035) values were statistically significantly different between the groups. NLR and PLR values were found to be higher in the unstable fracture group than in the stable fracture group. It was observed that values of 6.45 and above for NLR and 172.2 and above for PLR were predictive of unstable fracture.Conclusion: In conclusion, NLR and PLR are useful biomarkers in determining the severity of proximal femur fractures. It can guide us in the management of proximal femur fractures because it can be routinely, inexpensively and easily measured.
Keywords: Femur; Fracture; Neutrophil; Lymphocyte; Neck Fractures